2020
DOI: 10.1158/1538-7445.am2020-580
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 580: Effects of oral crofelemer on neratinib-induced diarrhea in beagle dogs

Abstract: Crofelemer is a novel allosteric modulator of cystic fibrosis transmembrane conductance regulator (CFTR) that is approved as an antidiarrheal in HIV patients receiving antiretroviral therapy. Neratinib is an oral, irreversible pan-HER tyrosine kinase inhibitor approved for extended adjuvant treatment of early stage HER2+ breast cancer. The objective of this study was to evaluate the effects of crofelemer in reducing the incidence and severity of diarrhea following daily oral neratinib dosing for 28 days in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These findings indicate that daily administration of neratinib induced a severe clinical presentation of diarrhea, intestinal hemorrhage, and dehydration; however, these clinical symptoms did not produce mucosal changes. Preliminary results from this neratinib-crofelemer study have been previously reported (10).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…These findings indicate that daily administration of neratinib induced a severe clinical presentation of diarrhea, intestinal hemorrhage, and dehydration; however, these clinical symptoms did not produce mucosal changes. Preliminary results from this neratinib-crofelemer study have been previously reported (10).…”
Section: Resultsmentioning
confidence: 80%
“…Neratinib is an oral irreversible HER1, HER2, and HER4 tyrosine kinase inhibitor that requires loperamide prophylaxis due to the high incidence of severe diarrhea associated with the drug ( 10 ). However, prophylaxis and management guidelines using antimotility drugs, such as loperamide, an opiate agonist, are empirical interventions to reduce the severity of diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that daily administration of neratinib induced a severe clinical presentation of diarrhea, intestinal hemorrhage, and dehydration; however, these clinical symptoms did not produce mucosal changes. Preliminary results from this neratinib-crofelemer study have been previously reported [22]. A responder dog (as defined a priori) was any dog with an average of � 7 loose/watery stools per week, which equals � 1 loose/watery stool per day, for at least 2 weeks of the 4-week study period (1A.).…”
Section: Plos Onementioning
confidence: 99%